Integração e miniaturização de sensores comerciais de baixo custo para monitoramento hídrico - Ribeiro, Fernanda Renata Almeida (Universidade Federal de São Carlos, 2025)
This dissertation presents the development of a low-cost platform for water quality monitoring, utilizing the Arduino UNO R3 microcontroller and an integration of commercial sensors. The proposed system aims to offer an accessible and efficient solution for collecting data on essential water parameters, such as temperature, electrical conductivity, pH, and turbidity. The work details the sensor integration methodology, the firmware developed for data acquisition and processing, and the modular architecture that allows for expansion to different application scenarios. The system was designed to be robust and easily replicable, contributing to the democratization of environmental monitoring and the early detection of changes in water quality. Although detailed validation and calibration results are still being obtained, the platform demonstrates the potential to be a valuable tool in environmental studies and water resource management.
Integration and miniaturization of low-cost commercial sensors for water monitoring
Keywords: Sensores; Sensors; pH; Turbidez; Conductivity; Temperatura; Arduino; Temperature; Sensors; Arduino; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ELETROANALITICA; 6. Água Potável e Saneamento